Layered Double Hydroxides-Loaded Sorafenib Inhibit Hepatic Stellate Cells Proliferation and Activation In Vitro and Reduce Fibrosis In Vivo - Peng, Wei; Zhang, Shiwen; Zhou, Wei; Zhao, Xinchen; Wang, Kexue; Yue, Chengxu; Wei, Xinyu; Pang, Siyan; Dong, Wei; Chen, Sulian; Chen, Changjie; Yang, Qingling; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
A core feature of liver fibrosis is the activation of hepatic stellate cells (HSCs), which are transformed into myofibroblasts and lead to the accumulation of extracellular matrix (ECM) proteins. In this study, we combined in vitro cellular efficacy with in vivo antifibrosis performance to evaluate the outcome of sorafenib (SRF) loaded layered double hydroxide (LDH）nanocomposite (LDH-SRF) on HSCs. The cellular uptake test has revealed that sorafenib encapsulated LDH nanoparticles were efficiently internalized by the HSC-T6 cells, synergistically inducing apoptosis of hepatic stellate cells. Moreover, the apoptosis rate and the migration inhibition rate induced by LDHs-SRF were 2.5 and 1.7 times that of SRF. Western Blot showed that the TGF-β1/Smad/EMT and AKT signaling pathway was significantly inhibited in HSC-T6 cells treated with LDHs-SRF. For the in vivo experiment, LDHs-SRF were administered to rat models of CCl4-induced liver fibrosis. H&E, masson and sirius red staining showed that LDHs-SRF could significantly reduce inflammatory infiltrate and collagen fiber deposition and immunohistochemical results found that LDHs-SRF treatment significantly inhibited the protein expressions of α-SMA in the liver, these results suggesting that LDHs-SRF exhibited better anti-fibrotic effect than SRF alone and significantly inhibited the proliferation and activation of rat hepatic stellate cells and collagen fiber synthesis.